Influence of tunneling on behavior of adjacent pile structures - Low, Wuu Shin (2019)
Urban development has been increasing rapidly throughout the globe due to rapid increase of population especially in densely populated metropolitan cities. Within years of construction technology breakthrough, engineers have made high-rise and mega structures possible to realize. In addition, due to space constraint on the ground surface and due to the fact that some structures need to be built under the ground surface, underground constructions such as tunnels and deep excavations have become among major construction projects in many metropolitan cities where infrastructure development serves a vital role for today’s civilization survival. Recently, the advancement in tunnel construction technology has enabled human beings to travel faster and easier through mountains or even under the sea. However, because tunnels are constructed below the ground surface, it may potentially have negative impacts on the adjacent structures especially on pile supporting building foundation which are situated close to the tunnel. Therefore, proper assessment and monitoring of stress changes and displacement of the ground must be taken into careful consideration for construction of tunnels in urban areas.